2012
DOI: 10.1097/pgp.0b013e31821f4de2
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Lymphatic Vessel Density in Vulvar Squamous Cell Carcinomas

Abstract: Lymphatic vessels serve as major routes for regional dissemination, and therefore, lymph node status is a key indicator of prognosis. To predict lymph node metastasis, tumor lymphatic density and lymphangiogenesis-related molecules have been studied in various tumor types. To our knowledge, no previous studies have evaluated the role of intratumoral lymphatic vessel density (LVD) in the behavior of vulvar carcinomas. The aim of this study was to analyze intratumoral LVD in relation to patient survival and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In our previous experience with cancers of the vulva, cervix and endometrium, we found an inverse correlation between intratumoral LVD and lymph node metastasis and prognosis 9-11. To explain our previous results, we hypothesized that the intratumoral lymphatic vessels were non-functional and therefore had the potential to disturb local drainage, including the transport of neoplastic cells outside the tumor.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our previous experience with cancers of the vulva, cervix and endometrium, we found an inverse correlation between intratumoral LVD and lymph node metastasis and prognosis 9-11. To explain our previous results, we hypothesized that the intratumoral lymphatic vessels were non-functional and therefore had the potential to disturb local drainage, including the transport of neoplastic cells outside the tumor.…”
Section: Discussionmentioning
confidence: 85%
“…The quantification of LVD was performed as previously described by our group 9-11. Briefly, stained TMA histologic sections were analyzed using standard light microscopy (Nikon, Eclipse 200).…”
Section: Methodsmentioning
confidence: 99%
“…Podoplanin is a glycoprotein that is recognized by the monoclonal antibody D2–40, which is considered the most reliable marker of lymphangiogenesis . Zhao et al examined podoplanin expression in OSCC and reported the proliferation of intratumoral and peritumoral lymphatics, suggesting that the spread of metastatic cells also occurs via intratumoral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Podoplanin is a 38-kDa membrane glycoprotein that is recognized by the monoclonal antibody D2-40, which has been used in research and clinical practice to distinguish lymphatic endothelium from endothelial cells of blood vessels (the latter does not express podoplanin). 14,18,22,23 Patients with a high lymphatic vessel density (LVD) are at increased risk for lymph node metastasis, supporting the hypothesis that LVD mediates lymphatic spread in oral carcinoma. 17,21,22,24 Based on findings that metastatic spread of head and neck tumors usually occurs via the lymphatic system and because lymphangiogenesis studies in various cancers have generated contradictory results, we measured the expression of lymphangiogenesis markers in HNSCC by immunohistochemistry.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation